THE STUDY OF USING FIBER STEM OF KEPOK BANANA (MUSA BALBISIANA) AS FISHING GEAR MATERIAL - Zaki, Hadi Sutaji; Syofyan, Irwandy; ', Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted in August 2015 in the laboratory materials fishing gear aquatic resources utilization department of fisheries and marine science faculty of the university riau pekanbaru, purpose of this study was to determine, sinking speed, elongation and breaking strength kepok banana stem fiber. The method used in this study is the experimental method. Where researchers made the experiment and observe directly. From histological contained protective tissue (epidermis), the basic network (parenchyma), and carrier networks (xylem and phloem) and has an air cavity to the breaking strength of the banana stem fibers that have been spun get an average of 3 kgf and elongation of 1.97 cm and the average speed of sinking 4.86 cm / sec based on the value of the banana stem feasible for use as fishing gearKeywords: banana stem kepok, breaking strength, elongation, sinking speed, histology observation